Food-related behaviors of rural (Asaase Kooko) and peri-urban (Kaadjanor) households in Ghana - Osei, Prince Kwabena; McCrory, Megan A.; Steiner-Asiedu, Matilda; Sazonov, Edward; Sun, Mingui; Jia, Wenyan; Baranowski, Tom; Frost, Gary; Lo, Benny; Anderson, Alex Kojo (Frontiers in Nutrition, 2025)
Background“Food-related behaviors” range widely and include food acquisition, storage, cooking, meal sharing, eating practices, among others. Food-related behaviors can influence nutritional status and health outcomes, and likely vary between rural and peri-urban households; however, there is limited documentation on such differences.ObjectiveTo assess food-related behaviors of rural and peri-urban households in Ghana to inform the design and implementation of a field study to validate passive wearable camera technologies for dietary assessment.MethodsThis was a cross-sectional qualitative study in rural (Asaase Kokoo) and peri-urban (Kaadjanor) communities, Ghana. Forty key informants (20 rural and 20 peri-urban) were interviewed about their household food-related behaviors. All interviews were audio-recorded and transcribed verbatim by professional transcribers, and manually coded using the directed content analysis approach.ResultsAll but three key informants were mothers, who were also the main food preparers for their households. The mean (SD) ages of female key informants were 35.5 (19.8) years in rural households and 38.9 (19.2) years in peri-urban households. The ages of two male key informants in rural households were 45 and 60 years, and the age of the only male key informant in a peri-urban household was 53 years. The most prevalent occupation in rural households was farming, while in per-urban households, blue-collar jobs (e.g., beauticians, sales personnel, and commercial drivers) were the main occupations. Farming was the main source of food in rural households, whereas buying food from local markets and grocery stores was the main source of food in peri-urban households. Some in rural and peri-urban households reported that husbands received preferential treatment by being served first with larger meal portions after food preparation in the home. Few key informants in rural households reported that meal-sharing patterns were based on ages of household members, with adults usually served more food than children.ConclusionThe meal-sharing patterns and eating practices reported in some rural and peri-urban households could potentially impact the nutrition and health of children. Our findings suggest the need for nutrition education for mothers to provide adequate and nutrient-rich foods to support optimal child growth and development.